The Publications of the Bedfordshire Historical Record Society. - Emmison, F. G. (Publications Bedfordshire Hist Rec Soc Ser., 1933)
The Publications of the Bedfordshire Historical Record Society, vol. 15 'The relief of the poor at Eaton Socon, 1706-1834', by F. G. Emmison. 'Tithe at Pavenham, 1759/60', contributed by C. D. Linnell. [Transcriptions of two documents held by Trinity College, Cambridge. The first is a report on the tithes at Pavenham written by W. Elstobb, a surveyor, of Cambridge in 1759. The second, probably also by Mr Elstobb, puts forward a scheme for renting the tithe from Trinity College which would allow each farmer to rent his share of the tithe, ie pay an agreed sum of money annually. The documents also record produce, prices and land values.]